The Correlational of Chinese Junior Hight School Students’ Motivation, Attitudes Toward the Learning Situation with English as a Foreign Language Academic Achievement - Lin, Yanqiu; Richard Lynch (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The purpose of this quantitative correlational study was to determine whether there was a significant relationship between Grade 9 students’ motivation and attitudes toward the learning situation for learning English as a foreign language with English academic achievement at a private school in China. A total of 110 Grade 9 students participated in this study. Students’ motivation and attitudes toward the learning situation for learning English as a Foreign Language Questionnaire which was adapted from Gardner’s (2004) international version of Attitude/Motivation Test Battery (Gardner, 2010) was used in this study consisting of 50 items (Gardner 2004, 2010) under five subscales. The researcher collected data from Grade 9 students studying in the 2021-2022 academic year at a private school in China. For the analysis of the collected data, descriptive statistics, and correlational analysis (using multiple correlation coefficient) was used. The findings of the research indicated that there was a weak correlation among the students’ motivation and attitudes toward the learning situation for learning EFL with English academic achievement. Based on the findings, the researcher provides recommendations for students, teachers, school administrators, future researchers.